Response Surface Methodology and Central Composite Design Analysis of Biosorption of Reactive Anthraquinone Dyes by Citrus sinensis Waste Biomass - Asgher, Mahwish; Nawaz Bhatti, Haq; Ahmad Bhatti, Ijaz; Ahmad Sheikh, Munir (Asian Journal of Chemistry, 2010)
The objective of present research work is to optimize the physicochemical parameters influencing the biosorption of reactive anthraquinone dyes by Citrus sinensis biosorbent using central composite design under response surface methodological approach. The quadratic model explained the biosorption data with high regression coefficients, R2 0.9882 for reactive blue 19 and 0.9999 for reactive blue 49. Interactive effect of pH, biosorbent dose and dye concentration was found significant and sorption capacity was optimum at acidic pH range, smaller biosorbent dose and higher dye concentrations. The 2-factor interaction of pH, biosorbent dose and dye concentration significantly influenced the sorption potential of biosorbent.